THE EXISTENCE OF BATAK TOBA SOUVENIRS IN TOMOK MARKET AND THE PROBLEMS IT FACES - Nasrudin Nasrudin; Reniwati Lubis; Gunawan Gunawan (Yayasan Education and Social Center, 2021)
Products in Indonesia's creative industries are generally handicrafts, an expression of local cultural products with the aesthetic value from various arts. One of the famous traditional handicraft markets in North Sumatra is Tomok Market. Tomok Market is a crowded market visited by the tourists who come to Samosir Island, Lake Toba. This research was motivated by invading souvenir products from Java and Bali as a rival for local products in traditional markets, Tomok Samosir. This research is a qualitative descriptive study that examines the original description of various typical Batak Toba souvenirs sold in the Tomok Market, analyzes the number of Batak Toba souvenirs and compares them with other souvenirs available in the Tomok Market, and to find out what problems that cause a decrease in the presence of Batak Toba souvenirs. The results indicate the number of Batak Toba souvenirs such as Tunggal Panaluan, wood lizard carving, Replica of Bataknese Traditional House, Bataknese Calendar, and Hasapi is not as many as souvenir products from Java and Bali. This product is due Batak craftsmen who make souvenirs has decreased. Another factor is the lack of availability of indigenous wood as the primary material for making souvenirs, and the number of wood hunters in the region is declining. As a result, Batak Toba souvenirs were more expensive than other souvenirs from Java and Bali, and sales declined. In addition, the lack of advertising and information media that explain the cultural value and uniqueness of these local products diminishes the interest of tourists